NOTES RELATING TO THE FLORA OF BHUTAN: XLII. SCROPHULARIACEAE, EXCLUDING PEDICULARIS - MILL, R. R. (Edinburgh Journal of Botany, 2003)
Seven new species and one new subspecies in Scrophulariaceae from the Flora of Bhutan area are described. They include two new species of Euphrasia, E. chumbica R.R. Mill sp. nov. (Chumbi, Sikkim and C Bhutan) and E. melanosticta R.R. Mill sp. nov. (Sikkim, N Bhutan); one new species of Kickxia, K. papillosa R.R. Mill sp. nov. (E Bhutan); one new species of Lagotis, L. chumbica R.R. Mill sp. nov. (Chumbi); one new species of Neopicrorhiza, N. minima R.R. Mill sp. nov. (N Bhutan); two new species of Scrophularia, S. cooperi R.R. Mill sp. nov. (C Bhutan) and S. subsessilis R.R. Mill sp. nov. (N Bhutan); and a new subspecies of Ellisiophyllum pinnatum (Wall.) Makino, subsp. bhutanense R.R. Mill subsp. nov. (Bhutan). Alectra avensis (Benth.) Merr., Bacopa monnieri (L.) Pennell, Scrophularia himalayensis Royle, Striga asiatica (L.) Kuntze and S. densiflora Benth. are all recorded from Bhutan and/or Sikkim for the first time. A brief argument is given for the continued use of hyphenated fel-terrae as the correct spelling of that epithet in Picria.
Keywords: Alectra; Bacopa; Bhutan; China; Dopatrium; Ellisiophyllum; Euphrasia; hyphenation (ICBN Art. 60); Kickxia; Lagotis; Neopicrorhiza; orthography; Picria; Scrophularia; Sikkim; Striga